2007
DOI: 10.2165/00003495-200767030-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology, Pathogenesis and Treatment of Pseudomonas aeruginosa Infections

Abstract: Pseudomonas aeruginosa is an important bacterial pathogen, particularly as a cause of infections in hospitalised patients, immunocompromised hosts and patients with cystic fibrosis. Surveillance of nosocomial P. aeruginosa infections has revealed trends of increasing antimicrobial resistance, including carbapenem resistance and multidrug resistance. Mechanisms of antimicrobial resistance include multidrug efflux pumps, ss-lactamases and downregulation of outer membrane porins. Mechanisms of virulence include s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
591
0
17

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 734 publications
(628 citation statements)
references
References 136 publications
5
591
0
17
Order By: Relevance
“…The most effective methods prevent or limit infection or the consequences of infection, whereas the more experimental and newer approaches attempt to correct the defective airway epithelial response to P. aeruginosa and produce an environment more akin to that of the WT-CFTR-expressing lung ( Table 1). As for modern methods of treating established CF lung disease, several recent publications have reviewed the current practices and latest clinical evidence for efficacious treatments [62][63][64][65].…”
Section: Intervention Strategies For Enhancing Resistance To P Aerugmentioning
confidence: 99%
“…The most effective methods prevent or limit infection or the consequences of infection, whereas the more experimental and newer approaches attempt to correct the defective airway epithelial response to P. aeruginosa and produce an environment more akin to that of the WT-CFTR-expressing lung ( Table 1). As for modern methods of treating established CF lung disease, several recent publications have reviewed the current practices and latest clinical evidence for efficacious treatments [62][63][64][65].…”
Section: Intervention Strategies For Enhancing Resistance To P Aerugmentioning
confidence: 99%
“…[18][19][20] P. aeruginosa is a medically important pathogenic bacteria, causing a broad spectrum of diseases, especially in immunocompromised individuals. 4,5 A prospective study showed that P. aeruginosa isolates recovered from the turbine waterlines caused gingival abscesses only in two immunocompromised patients, while a transient colonisation of the oral cavity of 78 healthy patients did not provoke any adverse health consequences. 4 Although the infective dose for colonisation in healthy individuals (>1.5 × 10 6 cfu/ ml) is rarely encountered in DUWLs, 21 it could be plausible that previous antibiotic treatment made the present patient more susceptible, thus lowering the required P. aeruginosa infectious dose.…”
Section: Resultsmentioning
confidence: 99%
“…5 However, antibiotic therapy with imipenem designed on the basis of in vitro antibiotic susceptibility tests led to successful infection eradication. The ability shown by P. aeruginosa to grow as highly antibiotic-resistant biofilm communities on the mucosa of patients with chronic sinusitis 23 could provide a plausible explanation for the very long-term (one year) antibiotic therapy needed before achieving infection eradication.…”
Section: N B R I E F Practicementioning
confidence: 99%
See 1 more Smart Citation
“…5 P. aeruginosa is a leading cause of nosocomial and burn wound infections, and chronically infects those afflicted with cystic fibrosis. 6 Treating these infections therapeutically is challenging, as many strains of P. aeruginosa are drug resistant. This magnifies the need for an effective vaccine.…”
Section: Introductionmentioning
confidence: 99%